Reevaluating 'countermeasure from below': evidences from judicial personnel reforms in China. (5th December 2019) - Wang, Yueduan
ABSTRACT: In the past few years, China has made a drastic switch to a more centralized approach to institutional change, thus vastly reducing the decades-old problem of local non-compliance. Using the recent judicial personnel reforms (员额制改革) as a case study, this paper examines the functioning of this new top-down model. Based on field research, the paper finds that the reforms have drastically reduced judge headcounts, placing tremendous burden on those remaining. In addition, they have made it much harder for new recruits to rise to the rank of judge, forcing them to remain as 'judicial assistants' who are not allowed to adjudicate cases independently. These changes have driven many judges to resign and have significantly diminished the appeal of judicial posts to new talent, especially in developed regions where caseloads are heavier and alternative career options more lucrative. Furthermore, such problems have continued to plague the judiciary despite long-standing widespread acknowledgment of them within and outside the judiciary. These developments highlight a critical disadvantage of the new top-down approach: unlike the previous decentralized system, under which powerful local actors could often de facto reject institutional changes they deemed flawed or unsuitable to local circumstances, the new centralized approach provides little effective check against design defects in the center's reforms.